2013
DOI: 10.1002/oby.20362
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet partially attenuates fermentation responses in rats fed resistant starch from high-amylose maize

Abstract: Objective The effects of type 2 resistant starch from high-amylose maize (HAM-RS2) in rodents fed with low-fat diets were demonstrated in previous studies. Fish oil is also reported to reduce body fat. In the current study, the effects of high fat and fish oil on HAM-RS2 feeding in rats were investigated. Design and Methods Rats were fed 0 or 27% (weight) HAM-RS2 with low (15% energy) or high fat (42% energy) diets that included 0 or 10% (energy) tuna oil to test the effect of HAM-RS2 in diet-induced obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 18 publications
6
62
2
Order By: Relevance
“…Most of these findings have been confirmed with different non-digestible carbohydrates (i.e., resistant starches and arabinoxylans) and will not be discussed in the present review [28], [29], [30], [31], [32], [33], [34].…”
Section: Gut Microbiota Communication and Gut Peptides: Impact On Hosmentioning
confidence: 72%
“…Most of these findings have been confirmed with different non-digestible carbohydrates (i.e., resistant starches and arabinoxylans) and will not be discussed in the present review [28], [29], [30], [31], [32], [33], [34].…”
Section: Gut Microbiota Communication and Gut Peptides: Impact On Hosmentioning
confidence: 72%
“…We have previously reported that fermentation of RS occurs in several rodent models , but not in two obese mouse models of polygenic obesity, New Zealand Obese (NONcNZO10/LtJ) and NON/ShiLtJ . Considering these results, we hypothesized that an animal model of obesity and diabetes, obese ZDF rats, may be dysbiotic and poorly ferment RS (poor fermentation of RS would be indicated by cecal contents pH usually above 7 and good fermentation below 6.5) . However, our alternate hypothesis was that if obese ZDF rats could ferment RS, then the fermentation would be associated with some reduction in abdominal fat and increased insulin sensitivity in the rats.…”
Section: Discussionmentioning
confidence: 92%
“…However, our alternate hypothesis was that if obese ZDF rats could ferment RS, then the fermentation would be associated with some reduction in abdominal fat and increased insulin sensitivity in the rats. Several of our previous studies demonstrated reduced body fat was associated with fermentation of RS in studies with Sprague Dawley rats , C57BL/6J mice , and Goto‐Kakazaki (GK) rats . There was also increased insulin sensitivity and pancreatic mass in the (GK) rat, which is a lean model of type 2 diabetes .…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, in the current study, there were marked ETWB-related changes in host physiology and liver metabolism that were concurrent with gut microbiome shifts, with no difference in total cecal SCFA abundance, indicating that factors independent of SCFAs were involved. Potential explanations for the lack of change in SCFAs include the following: impairment of microbial fermentation due to the presence of high fat in the diet (82) and increased uptake and utilization by colonic epithelial cells and/or bacteria. Beyond SCFAs, we identified a variety of candidate xenometabolites that are altered by changes in the gut bacteria and that reach the systemic circulation.…”
Section: Figurementioning
confidence: 99%